The process of translating the Experiences in Close Relationship (ECR) Scale into isiXhosa - Hadebe, Mandisa Zandile (Rhodes University, Faculty of Humanities, Department of Psychology)
Intimate relationships are highly influenced by each individual's attachment style. These attachment styles play a significant role in how romantic partners engage with each other and yet there are few tools that measure them. Not only are the tools few but also, they are not easily available in South African languages. Implementing isiXhosa language screening tools widens and enhances mental healthcare access for isiXhosa-speaking populations. This study aimed to develop an isiXhosa language version of the Experiences in Close Relationship Scale (ECR). The ECR is a 36-item self-report questionnaire designed to assess adult attachment styles in the context of close relationships. The scale evaluates the presence of anxious and avoidant attachment styles in adult romantic relationships. Anxious attachment is characterized by heightened anxiety about the relationship and a constant need for reassurance, while avoidant attachment involves a tendency to distance oneself emotionally from partners, often leading to difficulties in forming close connections. By measuring these styles, the scale provides deeper insights into how individuals relate to their partners and navigate intimacy in their romantic lives. The ECR was translated into isiXhosa using a four-stage translation design, which included: 1. Forward translation, 2. Back translation, 3. Committee meetings, and 4. Qualitative piloting of the resultant translation in a small sample of first language isiXhosa speakers. A quantitative pilot will follow this study. The results indicate that while broad concept equivalence was easier to achieve, participants struggled with understanding some of the items due to the difference in academic, written language and spoken language. The questions about emotions proved more difficult to translate. South African languages differ in dialect across different areas of the country. The isiXhosa terms chosen for this translation often conveyed distinct meanings or could be interpreted differently, depending on the specific geographical region and local dialect. This rich linguistic diversity posed a considerable challenge throughout the translation process, as it required careful consideration of context and cultural nuance to ensure accurate communication.
Keywords: Interpersonal relations -- South Africa; Psychological tests Translating; Xhosa language; Xhosa (African people) Mental health; Intimacy (Psychology)